Tarqiyyatu Istii'aabi al-Mufradaat al-'Arabiyyat 'Ibr Barnaamaj al-Haatif al-Dzakiyy - Rokhani Rokhani; Achmad Zuhrudin; Jamaluddin Shiddiq (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2023)
This development research aims to produce learning media mobile learning based on Android for students as well as to know the quality of mobile learning media products that have been produced so feasible use in vocabulary learning. This study is a research development or Research and Development (R & D) adapted from ADDIE development model. The stages are 5 stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. As for the general procedures in designing this application program, it is divided into three: collecting data, recording data using Adobe Flash CS6, and entering coding, or we call it an Action Script. Validation is done by material experts and media experts and students. The results showed that the learning media mobile learning based on Android that has been developed based on the assessment of media experts 84 % with the category of Excellent and the material expert assessment of 86.9 % with Excellent category. And also students assessment of 94.9 % with Excellent category الملخص يهدف بحث التطوير هذا إلى إنتاج تعليم متنقل للوسائط التعليمية يعتمد على Android للطلاب بالإضافة إلى معرفة جودة منتجات وسائط التعلم المحمولة التي تم إنتاجها بحيث يمكن استخدامها في تعلم المفردات. هذه الدراسة عبارة عن تطوير بحث أو بحث وتطوير مقتبس من نموذج تطوير ADDIE. المراحل 5: 1) التحليل ، 2) التصميم ، 3) التطوير ، 4) التنفيذ ، 5) التقييم. أما بالنسبة للإجراءات العامة في تصميم هذا البرنامج التطبيقي ، فهي تنقسم إلى ثلاثة: جمع البيانات ، وتسجيل البيانات باستخدام Adobe Flash CS6 ، وإدخال الترميز ، أو نسميها Action Script. يتم التحقق من صحة المواد من قبل خبراء المواد وخبراء الإعلام والطلاب. وأظهرت النتائج أن التعلم عبر وسائل الإعلام المتنقلة القائم على نظام أندرويد تم تطويره بناءً على تقييم خبراء الإعلام 84٪ بفئة ممتاز وتقييم خبير المادة 86.9٪ بفئة ممتاز. وكذلك تقييم الطلاب 94.9٪ بفئة ممتازة